Pembentukan Karakter Peserta Didik Melalui Pembelajaran IPS di SD - Emha Balqis, Arini; Usriyah, Lailatul; Mu’alimin, Mu’alimin (Diksi: Jurnal Pendidikan dan Literasi, 2025)
Formation of the character of students in terms of religion, ethics, morals and manners in interacting with the community, education is designed and implemented by forming characters by the values of the nation's cultural character, especially in IPS learning. The formation of the character of students through habituation and example as outlined in IPS learning which is the initial stage of IPS learning based on Curriculum 13 which cannot be separated from the role of the class teacher itself and forms into IPS learning guided by BSNP through the Semester Program (PROSEM), Syllabus and RPP (lesson plan). The supporting factors for character include exemplary and guiding awareness from teachers, good coordination from all school parties, and cooperation from each school component in shaping the character of students with higher commitment. The inhibiting factors for the formation of the character of students are the lack of self-awareness of the students, the limited ability of the teacher to act decisively against students who violate and the influence of the environment around students.